A Listing of the Printed Editions of Nicolaus de Lyra - Gosselin, Edward A. (Traditio, 1970)
Nicolaus de Lyra (ca. 1270–1349) is a figure of great importance for the history of Bible study. Regarding Nicolaus' origins and background, as well as over the dates of his birth and death, there has been much confusion. It is only in this century that the research of scholars has lifted the veil which shrouded the life of this eminent Franciscan, so that now we are able to present a brief but accurate chronology of his career.